2017
DOI: 10.1186/s12941-017-0214-0
|View full text |Cite
|
Sign up to set email alerts
|

Patients with community-acquired bacteremia of unknown origin: clinical characteristics and usefulness of microbiological results for therapeutic issues: a single-center cohort study

Abstract: Bacteremia of unknown origin (BUO) are associated with increased mortality compared to those with identified sources. Microbiological data of those patients could help to characterize an appropriate empirical antibiotic treatment before bloodcultures results are available during sepsis of unknown origin. Based on the dashboard of our ward that prospectively records several parameters from each hospitalization, we report 101 community-acquired BUO selected among 1989 bacteremic patients from July 2005 to April … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 19 publications
3
14
0
Order By: Relevance
“…Consistent with previously published data [28], Enterobacterales were the most commonly isolated pathogens in cases of true bacteraemia ( n = 439, 59.3%) followed by Staphylococcus aureus ( n = 92, 12.4%). Streptococcus species accounted for 13.5% of true bacteraemia with Streptococcus pneumoniae ( n = 19) being the most frequently isolated, followed by Streptococcus pyogenes ( n = 16).…”
Section: Resultssupporting
confidence: 92%
“…Consistent with previously published data [28], Enterobacterales were the most commonly isolated pathogens in cases of true bacteraemia ( n = 439, 59.3%) followed by Staphylococcus aureus ( n = 92, 12.4%). Streptococcus species accounted for 13.5% of true bacteraemia with Streptococcus pneumoniae ( n = 19) being the most frequently isolated, followed by Streptococcus pyogenes ( n = 16).…”
Section: Resultssupporting
confidence: 92%
“…However, corticosteroids not only decrease inflammation but also have side effects, including a reduction in the activity of the immune system, as well as hyperglycemia. A previous study reported that an unknown focus of bacteremia was associated with inappropriate antibiotic therapy and poor clinical outcome [ 36 ]. These findings suggest that the risk factors associated with mortality provide useful information for clinicians to avoid treatment failure, thereby enabling appropriate medical therapy after the onset of bacteremia.…”
Section: Discussionmentioning
confidence: 99%
“…Hospital-acquired BSI was defined as the bacteremia and fungemia that occurred after 48 h of admission. BSI was defined when no focus of infection could be specified with medical history, physical examination, clinical data, microbiological tests, and imaging [10, 12]. Owing to the retrospective nature of the study, the consent of patients was not required.…”
Section: Methodsmentioning
confidence: 99%
“…However, independent risk factors for BSI-associated mortality, especially in case of BSI of unknown origin, remain uncertain. BSIs of unknown origin are prevalent in HD patients and are associated with high mortality as compared to those with identified origin of infection [10]. Therefore, it is important to detect the origin of BSI.…”
Section: Introductionmentioning
confidence: 99%